Evaluation of the Difference between Predicted and Measured Central Corneal Thickness Reduction after SMILE and Femtosecond Laser-assisted LASIK for Myopia. (3rd August 2021) - Wu, Fang; Yin, Houfa; Yang, Yabo
ABSTRACT: Purpose: To evaluate the agreement between the predicted and measured central corneal thickness (CCT) reduction after the small incision lenticule extraction (SMILE) surgery and femtosecond laser-assisted in situ keratomileusis (FS-LASIK) surgery. Methods: A total 165 patients were enrolled in this prospective study. Eighty patients with a mean spherical equivalent (SE) of −4.72 ± 1.80 Diopters (D) were treated with the FS-LASIK procedure and Eighty-five patients with a mean SE of −4.78 ± 1.63 D were treated with SMILE procedure. One eye for each patient was randomly selected and included for statistical analysis. Ultrasound pachymetry measurement and Scheimpflug camera corneal topography were performed preoperatively and 3 months postoperatively. The measured CCT reduction was calculated by comparing the preoperative examinations with postoperative examinations. Comparative statistics and linear regression analyses were performed. Results: The mean predicted CCT reduction was 95.02 ± 21.39 μm in FS-LASIK group and 103.49 ± 22.87 μm in SMILE group ( P = .015). The prediction of laser platform was found to overestimate the measured CCT reduction for both FS-LASIK group (ultrasound 13.20 ± 9.34 μm) and SMILE group (ultrasound 13.12 ± 8.68 μm). The prediction of laser platform was found to systematically overestimate the measured CCT reduction in FS-LASIK group. In SMILE group, the difference between predicted and measured CCT reduction were found significantly related with the predicted CCT reduction ( P < .001 for ultrasound; and P = .004 for Pentacam). Conclusion: A systematic overestimation of measured CCT reduction in FS-LASIK group did not influence the refractive precision of FS-LASIK. Due to the different biomechanical distributions in post-SMILE cornea, the measured CCT reduction was influenced as the changes in refractive correction. Nomogram adjustment for high myopic correction needs further research.